Effectiveness of discovery learning using a mobile otoscopy simulator on knowledge acquisition and retention in medical students: a randomized controlled trial - Josie Xu; Paolo Campisi; Vito Forte; Brian Carrillo; Allan Vescan; Ryan Brydges (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Portable educational technologies, like simulators, afford students the opportunity to learn independently. A key question in education, is how to pair self-regulated learning (SRL) with direct instruction. A cloud-based portable otoscopy simulator was employed to compare two curricula involving SRL. Pre-clerkship medical students used a prototype smartphone application, a 3D ear attachment and an otoscope to complete either otoscopy curriculum. Methods Pre-clerkship medical students were recruited and randomized to two curriculum designs. The “Discovery then Instruction” group received the simulator one week before a traditional lecture, while the “Instruction then Discovery” group received it after the lecture. To assess participants’ ability to identify otoscopic pathology, we used a 100-item test at baseline, post-intervention and 2-week retention time points. Secondary outcomes included self-reported comfort, time spent using the device, and a survey on learning preferences. Results Thirty-four students completed the study. Analysis of knowledge acquisition and retention showed improvement in scores of both groups and no significant effects of group (F1,31 = 0.53, p = 0.47). An analysis of participants’ self-reported comfort showed a significant group x test interaction (F1,36 = 4.61, p = 0.04), where only the discovery then instruction group’s comfort improved significantly. Overall device usage was low, as the discovery then instruction group spent 21.47 ± 26.28 min, while the instruction then discovery group spent 13.84 ± 18.71 min. The discovery first group’s time spent with the simulator correlated moderately with their post-test score (r = 0.42, p = 0.07). After the intervention, most participants in both groups (63–68%) stated that they would prefer the instruction then discovery sequence. Conclusions Both curricular sequences led to improved knowledge scores with no statistically significant knowledge differences. When given minimal guidance, students engaged in discovery learning minimally. There is value in SRL in simulation education, and we plan to further improve our curricular design by considering learner behaviours identified in this study.